Le Journal et les aquarelles de Robert Hood : une œuvre du paradoxe - Françoise BESSON (E-REA)
Robert Hood was a member of the first Franklin expedition in search of the North West Passage. His journal, his paintings and drawings, while products of colonial times, may nevertheless be considered collectively as a treatise of respect and tolerance providing interesting keys to otherness. Hood discusses difference, exchange and principally respect for both humans, whatever his or her culture, and animals. Though primarily a journal for the Admiralty and the English reading public, Hood’s text and pictures suggest a wider, philosophical reading of otherness. This unfinished text addresses the paradox of a colonial text eventually becoming a philosophical work, engaging with otherness.